Análisis del tratamiento de la infomación sobre el proceso eruptivo del volcán Tungurahua en diario el heraldo año 1999 - 2000” - Mary Augusta, Barrera Freire (2020)
The objective of this project is to analyze the management of information on the eruptive process of the Tungurahua volcano in Diario El Heraldo in the years 1999 - 2000, as well as to identify and analyze each of the contents that were disseminated during this period, in which a variety of contents stand out in different topics. In the same way, each one of the experiences lived by those who were part of this time in history, especially those who lived in the affected cities, as well as those who made the decisions for the people, stands out. Each one of the different publications made by the medium gathers the different events that were evidenced from the beginning to the end of the eruptive process of that time, highlighting the support and aid that was implemented by various public and private institutions not only in the province, but also in Ecuador and the world. Finally, a printed communication product will be produced, highlighting the main publications produced by the printed media.